Paraneoplastic Bullous Pemphigoid Resembling Erythema Gyratum Repens-like Figurate Erythema - Jantrakulroj, Sarun; Thammarucha, Sasima; Kampirapap, Kowit; Kattipathanapong, Pinnaree (Thai Journal of Dermatology, 2023)
Paraneoplastic bullous pemphigoid is a rare autoimmune blistering disease that is associated with an underlying malignancy. The clinical presentation can vary, but typically involves the appearance of multiple tense blisters and erosions. This case report describes an atypical manifestation of bullous pemphigoid characterized by the presence of bullous and erythematous figurate lesions closely resembling the clinical features of erythema gyratum repens-like figurate erythema, which poses diagnostic challenges. The histopathological examination, direct immunofluorescence and indirect immunofluorescence consistent with bullous pemphigoid. By integrating the patient’s underlying condition of lung cancer with the clinical presentation and histologic finding, the diagnosis of paraneoplastic bullous pemphigoid resembling erythema gyratum repens-like figurate erythema was made. The treatment of paraneoplastic bullous pemphigoid involves addressing and treating underlying malignancy.